Features and methodological approaches to determining the indicators and the level of capacity of the territorial communities of Ukraine - Baranovskyi, Mykola (Human Geography Journal, 2022)
The capacity of territorial communities is the main indicator of the success of the decentralization reform. Applying the current methodology to determine the capacity of communities showed its essential and technical flaws. The methodology was developed at the beginning of administrative decentralization; therefore, it does not reflect the real capacity of communities, but the presence of conditions for their formation. The primary basis for an objective determination of community capacity is the selection of the relevant indicators and methodological approaches to the development of its assessment scale. The article analyses the approaches of academics and practitioners to determining the list of indicators for the assessment of community capacity. It was established that the set of indicators depends on the scientists' interpretation of the concept of "capable community", it is characterized by fragmentation (financial indicators dominate) and is developed without proper reasoning.Considering these features, the study justified the appropriateness of using the econometric methods and the results of monitoring the activities of communities to analyse their capacity. An information base (27 indicators across 25 communities of Poltava, Volyn and Lvov regions) of the study, which can be considered representative in terms of the regional representation and different types of communities, was formed. Based on the application of correlation and factor analyses, ten (three socio-economic, two infrastructural, and five financial) indicators, which are among the most important indicators of community capacity, were identified. These indicators were selected considering the number of significant correlations and the value of factor loadings. The study established that the current approach to determining the level of community capacity does not enable a proper assessment of existing disproportions. The study proposes to determine the level of community capacity by calculating an integral indicator and to develop a scale of criteria taking into account its deviation from the average values for the country.